Criação de valor em cooperativa de crédito com o advento do open banking: estudo de caso em uma Cooperativa da Serra Gaúcha - Campigotto, Daiane (Universidade do Vale do Rio dos Sinos, 2021)
Open banking will promote a real revolution in the Brazilian financial market. With the use of data, products and services will be customized according to the consumer's needs, bringing greater satisfaction. With more competition, the search for lower interest rates and credit market decentralization will be feasible. In addition to the high investment in technology, financial institutions will be required to reposition themselves in relation to their business model, especially with regard to delivering value to the customer. Thus, this research sought to identify how Credit cooperatives can remain sustainable in the market with the implementation of open banking in Brazil, through actions to add value to their members, through a single case study. In the first stage of the study, research data applied to Sicredi employees were collected and analyzed. In step two, secondary data from research previously carried out by Sicredi Serrana with its associates in the agro segment were analyzed. The study identified that practically half of Sicredi's employees are unaware of actions by their cooperative or by the Sicredi system that are linked to preparation for open banking, which are not related to technology. This justifies the search for better communication with all levels of the company regarding the adopted strategy. There is synergy in the responses to the two surveys regarding solutions that Sicredi can offer to improve the lives of rural producers, which demonstrates the company's understanding of the needs of its members. In addition, it was possible to identify the differentiated performance of the credit cooperative that is preparing for open banking, which is the case of Sicredi Serrana, which since 2016 has started a differentiated work with rural producer associates, aiming to prepare for the new market. Thus, it is concluded that even though credit unions already act differently from other financial institutions, seeking greater proximity in the relationship with their members, open banking is a relevant subject, so much so that Sicredi joined even though it was not on the list. of financial institutions with mandatory entry currently, in accordance with the law. In addition, cooperatives can indeed strengthen their performance, seeking the development of their members and the community, through actions to add value, such as what is being done by Sicredi Serrana.
Keywords: Open banking; Cooperativa de crédito; Criação de valor; Segmento agro; Credit cooperative; Value creation; Agro segment; ACCNPQ::Ciências Sociais Aplicadas::Administração